(untitled) (Academia Journal of Medicine, 2019)
Background: Dengue is the most common mosquito-borne viral disease throughout the world. Dengue could be asymptomatic or it may manifest as non-severe, severe and fatal types. Severe dengue manifests itself in myriad ways. Excessive hospitalization of dengue patients occurs due to the absence of definite early prognostic markers or early predictors of severity/mortality. There are few Indian studies on mortality in severe dengue. The objective of this study was to explore Multi-organ dysfunction syndrome (MODS) in Dengue fever with an emphasis on comparison between survivors & non-survivors. Subjects and Methods: This study was done at JSS Hospital, a tertiary referral teaching hospital of JSSMC, JSSAHER with 80 adult ICU beds. It was a retrospective observational study. Patients with laboratory-confirmed severe dengue infections satisfying inclusion and exclusion criteria and admitted to the ICU between September 2016 and September 2017, including the large outbreak period were considered. The data were collected from inpatient case-records and the analysis was done, retrospectively. Results: A total of 29 patients met all inclusion and exclusion criteria. In our study, out of 29 cases, total number of males were 17 (58.6%), whereas females were 12 (41.4%). Mean age of patients was 43.37 years (SD:14.36). The mortality of severe dengue with MODS admitted to the ICU remains high (55.2%) in this study. In this study, mean age was more in survivors when compared to non survivors; At admission, Creatinine, Lactate & PCV were higher among non survivors; All patients with Hypotension, Both the patients with ARDS, myocarditis & All the 6 patients who had bleeding manifestations expired & prolonged a PTT and PT-INR were found among many non survivors; Other parameters like LFT, Se.Albumin and Comorbidities did not have any impact on mortality. In this study, though both the groups had hypoalbuminemia, Serum Albumin was not statistically significant between survivors & non-survivors while arterial Lactate, creatinine and PCV were significant. Conclusion: The mortality of severe dengue with MODS admitted to the ICU remains high. In this study, surprisingly, mean age was more in survivors when compared to non-survivors; Creatinine, Lactate & PCV were higher among non-survivors. Other parameters like LFT, Se.Albumin and Comorbidities did not have any impact on mortality. Definite early prognostic markers or early predictors of severity/mortality is the need of the day.